The Schumpeterian Stationary State Revisited - Whitaker, J. K. (The Review of Economics and Statistics, 1971)
This note is intended as comment on paper by P. A. Samuelson that was initially published almost 30 years ago.' Such delay in reaction may seem surprising. But in fact it is only in the last few years that our understanding of the subtle problem of decision making with infinite horizons has advanced sufficiently to bring to light certain difficulties in Samuelson's attempt to confound Robbins' criticisms of Schumpeter. J. A. Schumpeter, in his Theory of Economic Development had argued that the classical stationary state must always involve zero interest rate. Subsequently, L. C. Robbins argued in criticism of Schumpeter that the interest rate could never remain permanently at zero For if there were no yield to the use of capital . . . there would be no reason to refrain from consuming it. 3 Robbins was in turn taken to task by Samuelson and accused of being wrong, economically, mathematically, and logically. 4Samuelson, dazzling his audience with appeal to a simple iso-perimetric problem in the Calculus of Variations, Y was able to argue that: We have shown that there is no logical inconsistency in Professor Schumpeter's theory of interest on the side of supply. On the contrary, the strict assumption of absence of time preference implies no decumulation at zero rate of interest, and no cessation of accumulation at any positive rate of interest. 6 The particular case that Samuelson employed in his defence of Schumpeter was that with immortal individuals or constant-size families, all maximizing at any date t Ramsey preference function of form